Immunomodulatory Effect of Water Extract of Stachytarpheta jamaicensis (L.) Vahl - Suci Nar Vikasari & , AndreanusAndaja Soemardji, Afifah Bambang Sutjiatmo & , Suryani (Journal of Applied Pharmaceutical Science, 2015)
Stachytarpheta jamaicensis (L)Vahl traditionally is used to treat several diseases, such as urinary tract infections, rheumatic, and pharyngitis. The objective of this study was to test immunomodulatory effect of water extract of S. jamaicensis (L.) Vahl. herbs. Immunomodulatory assay of water extract of S. jamaicensis herbs have been examined in male Balb/c mice using carbon clearance assay. The doses of the extract were 62.5, 125, and 250 mg/kg bw. Parameter of immunomodulatory effect was phagocytic indexes after seven days administration of the extract. The result showed thatwater extract of S. jamaicensis at doses of 62.5 and 250 mg/kg bw had lower phagocytic index compared to Zymosan A, but higher phagocytic indexes compared to Methylprednisolone. The water extract of S. jamaicensis may be considered as an immunosuppresant agent.
Keywords: Stachytarpheta jamaicensis, immunomodulatory, carbon clearance, phagocytic index.